INFLUENCE OF INFLUENZAL INFECTION FOR PREGNANT ON THE STATE OF UTERINE-PLACENTAL AND FETO-PLACENTAL BLOOD CIRCULATION - Shpak, І.V. (World of Medicine and Biology, 2013)
The estimation of a condition of utero-placental and feto-placental blood circulation at 90 pregnant women from the pregnancy transferred to time, or an available influenzal infection is spent. Typical displays of infringement of utero-placentary and feto-placental blood circulation is threat of interruption of pregnancy, a fetus’ growth inhibition, prenatal hypoxia, threat antenatal destructions of a fetus. Infringement of utero-placental blood circulation it is revealed in ІІ trimester at 21,1 % of supervision, in ІІІ trimester - at 33,3 %. The systolo-diastolic parity has increased to 4,0. Pathological type of feto-placental blood circulation was diagnosed at 78,3 % of pregnant women. Hypoxia of fetus of various severity level it is revealed at 66,7 % of cases, sharp distressis of fetus - at 13,3 %, chronic distressis of fetus - at 53,3%.
Keywords: utero-placental; feto-placental blood circulation; a flu